Transformation of myelodysplastic syndrome (MDS) to acute myeloid leukaemia (AML) - Goh, Chermaine Yu Zhen (Nanyang Technological University, 2021)
Myelodysplastic syndrome (MDS) is a clonal haematopoietic stem cell disorder characterised by ineffective haematopoiesis. Patients with MDS have a probability of transforming to Acute Myeloid Leukaemia (AML). To better understand the transformation of MDS to AML in Singapore, a retrospective multivariate analysis was done on data of 215 MDS patients data obtained from the Cytogenetics Lab at Singapore General Hospital.